Ca[2+]-ATPase function is required for intracellular trafficking of the Notch receptor in Drosophila. - Periz, G.; Fortini, M.E. (The EMBO Journal, 1999)
Maintaining high Ca(2+) concentrations in the lumen of the endoplasmic reticulum is important for protein synthesis and transport. We identified a lethal complementation group recovered in a screen for mutations that reduce Notch activity as loss-of-function alleles of the Drosophila Ca(2+)-ATPase gene Ca-P60A. Analysis of Ca-P60A mutants indicates that Ca(2+)-ATPase is essential for cell viability and tissue morphogenesis during development. Cultured cells treated with Ca(2+)-ATPase inhibitors exhibit impaired Notch cleavage and receptor trafficking to the cell surface, explaining the genetic interaction between Ca(2+)-ATPase and Notch. Notch and several other transmembrane proteins are mislocalized in tissue clones homozygous for Ca-P60A mutations, demonstrating a general effect on membrane protein trafficking caused by a deficiency in Ca(2+)-ATPase.